Phosphodiesterases as drug targets - Francis, Sharron H. (Handbook of Experimental Pharmacology, 2011)
Cyclic nucleotide phosphodiesterases (PDEs) are promising targets for pharmacological intervention. Multiple PDE genes, isoform diversity, selective expression and compartmentation of the isoforms, and an array of conformations of PDE proteins are properties that challenge development of drugs that selectively target this class of enzymes. Novel characteristics of PDEs are viewed as unique opportunities to increase specificity and selectivity when designing novel compounds for certain therapeutic indications. This chapter provides a summary of the major concepts related to the design and use of PDE inhibitors.